FEATURES OF THE BODY IMAGE DEVELOPMENT AMONG PEOPLE WITH MUSCULOSKELETAL DISORDERS - Chukhrii Іnna (PSYCHOLOGICAL JOURNAL, 2017)
The human being has certain limitation of life activity, in particular the functions of the musculoskeletal system disorders, which affects on the formation of body image with the appearance of these features. The formation of body image among children with the musculoskeletal system disorders occurs with the slowdown, and people who have been injured, which led to the functional disabilities at young age, have a dynamics of loss experiences, post-traumatic stress disorders and mechanisms of destruction and restoration of already formed body image. The problem of formation and development of the body image in the works of D. Anzier, P. Blosom, D. Rozenfeld, Z. Freid and others is disclosed. The peculiarities of the formation of the body image among people with functional disabilities and the perception of their own body by people with visible appearance differences by S. Gilbert, G. Kent, P. Smith and Y. Thompson are described. The features of the formation of I-physical among people with functional disabilities in the scientific works of domestic scientists: O. Romanenko, Ye. Sinyova, Yu. Shvalb, A. Shevtsov. are described. Young people with congenital or acquired musculoskeletal system disorders have difficulties in creation of their own body image and, accordingly, a number of unfavorable symptoms. Young people with congenital musculoskeletal system disorders formed the complexity with the perception of the body image, due to unfavourable conditions of its formation, it can be assumed that body image is underdeveloped. It is also possible to assume that body image can be non-holistic with missing parts or the component composition of body image include prostheses and wheelchair that occupy the place of missing or underdeveloped organs. These features point to the need for early psychotherapeutic intervention, besides, psychotherapy is required not only for children with the psycho-physical development disorders, but also their parents. Young people with acquired musculoskeletal system disorders may experience the destruction of the body image, anxiety, fear, shame and loss of identity, which also requires personal psychotherapy.